Impact of Interest Rate on the General Stock Price Index on Damascus Stock Exchange (Journal of Hama University, 2024)
This study aimed to identify the effect of the interest rate on the general stock price index Dwx during the period from 2013 to 2021, the descriptive approach and reliance on appropriate statistical methods were used to achieve the goal of the study and to analyze and interpret the data to reach conclusions and proposals,to test the hypothesis we relied on the Spss statistical program considering that the interest rate is the independent variable and the general stock price index is the dependent variable, and the study found that there is no statistically significant effect of the interest rate on the general stock price index Dwx, and we can explain this unexpected result to the economic conditions that Syria went through the war and the weak effectivenes of the interest rate in Syria.
Keywords: interest rate; financial markets; general stock price index DWX